Introduction to VCD Version 2 in FV-30 Model - SONA S and DATTA RAJDEEP (2000)
INTERNAL GUIDE: GIRIJA H M, MVJCE EXTERNAL GUIDE: SASI V P, ENGG R&D BPL SANYO TECH LTD BANGALORE
Keywords: VCD Version 2